IS THERE ANY FUTURE FOR COAL POWER PLANTS IN EUROPE? - A. V. Zimakov (MGIMO University Press, 2017)
The article deals with the policies of EU countries towards coal power plants as well as practical steps taken by their governments. Coal power plants are widely considered to be environmentally harmful which confronts with environmental policies of the EU suggesting Europe-wide cuts of greenhouse gas emissions. Based on that assumption a number of EU countries such asBelgium,Austria,Portugal,Dania,Finland,SwedenandUKare striving to phase out coal power plants and achieved significant progress on this path replacing coal with other generation sources. On the other hand, other EU members are lagging behind as coal phase-out is not an urgent item of their political agenda. This situation is typical forIreland,Netherlands,Italy,Croatia,SloveniaandSlovakia. Domestic coal extracting industry can pose a significant hindering factor for a coal power plants phase-out and can effectively block the process. This is the case inBulgaria,Romania,Hungary,CzechRepublic,GreeceandPoland. ButGermany, which also has a well-developed coal industry, transforms its energy sector towards a green one cutting the share of coal in the generation mix. If this effort of the German government proves successful it will deliver a positive transformation model for other EU countries with a large share of coal in generation-mix due to domestic coal extraction industry. The analysis of the political and economic (both macro and micro) processes leads to conclusion that there is no unity among EU member states in their approach towards coal fired power plants phase-out. This will allow for coal power plants to retain their market share in a short to medium term. But in the longer run one can expect a significant decrease of coal fired generation inEurope, even in the countries traditionally dependent on coal.